The educational challenge of faculty workforce shortage in radiologic sciences: an empirical finding. - Undie W; Passmore G (Radiologic Science & Education, 2010)
In 2006, the Association of Educators in Imaging and Radiologic Sciences (AEIRS) commissioned a workforce committee to investigate the scope of educator workforce shortage in radiologic sciences. The primary purpose of the study was to provide empirical data on the demographic profile of radiologic science educators and to examine educators' perceptions of job satisfaction, and their intention for retirement. Seventy-five percent of educators surveyed are older than 45 years and 42% expressed interest in retiring within the next 10 years. Educators were found overall to be satisfied with their jobs. The greatest satisfaction rating was in the area of job security and inter-program cooperation, although salary ranked lowest in satisfaction among 11 indicators. It was evident from the study that planned retirement of educators and Program Directors were genuine concerns for many educators. Other concerns resonate around the additional education requirements imposed on Program Directors. It would appear that the radiologic sciences' educational corps is facing the challenge of a retiring cadre that has been predicted by the aging of the baby boomers. The implication, given the survey responses and comments, is that as a professional body, the emphasis of our professional discussions should focus on educator recruitment and contingency plans in case the needed recruitment does not come to fruition.